2023
DOI: 10.3390/cancers15245806
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Optimal Thermal Ablation Margins in Colorectal Liver Metastases: A Systematic Review and Meta-Analysis of 21 Studies

David-Dimitris Chlorogiannis,
Vlasios S. Sotirchos,
Christos Georgiades
et al.

Abstract: Background: Colorectal cancer (CRC) is the second most common cause of cancer-related deaths in the US. Thermal ablation (TA) can be a comparable alternative to partial hepatectomy for selected cases when eradication of all visible tumor with an ablative margin of greater than 5 mm is achieved. This systematic review and meta-analysis aimed to encapsulate the current clinical evidence concerning the optimal TA margin for local cure in patients with colorectal liver metastases (CLM). Methods: MEDLINE, EMBASE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Definitive evidence on the superiority of A0 margins came from a recent meta-analysis which included the pooled results of 21 studies examining the oncological outcomes of thermal ablation stratified by ablation margins. In this study, the authors confirmed that the risk for local tumor progression is at least 3.6 times higher when the minimal ablation margin is less than 5 mm (Risk Ratio: 3.60; 95% CI: 2.58-5.03; p-value < 0.001) [62]. When possible, the achievement of an A0 ablation margin is associated with a local tumor progression-free survival exceeding 95%; this represents an opportunity for local cure similar to surgery, but with a reduced morbidity and risk of complications [7].…”
Section: Image-guided Percutaneous Ablationsupporting
confidence: 69%
“…Definitive evidence on the superiority of A0 margins came from a recent meta-analysis which included the pooled results of 21 studies examining the oncological outcomes of thermal ablation stratified by ablation margins. In this study, the authors confirmed that the risk for local tumor progression is at least 3.6 times higher when the minimal ablation margin is less than 5 mm (Risk Ratio: 3.60; 95% CI: 2.58-5.03; p-value < 0.001) [62]. When possible, the achievement of an A0 ablation margin is associated with a local tumor progression-free survival exceeding 95%; this represents an opportunity for local cure similar to surgery, but with a reduced morbidity and risk of complications [7].…”
Section: Image-guided Percutaneous Ablationsupporting
confidence: 69%
“…Achieving a 5–10 mm MAM ensures the long-term success of MWA treatment and reduces the risk of local tumor progression and recurrence [ 17 , 22 , 23 , 67 ]. In the present study, a MAM of 5 mm was achieved clinically and computationally for all three patients, regardless of whether the therapy was completed at the scheduled ablation time (9.5 or 10 min) or the optimized ablation time (8 min for patients 1 and 2 and 7 min for patient 3).…”
Section: Discussionmentioning
confidence: 99%